Case Report: First report of Legionella micdadei pneumonia and organizing pneumonia in a patient with myelodysplastic and Sweet syndromes - Chen, Yingying; Liang, Sicong; Lu, Ye; Zhou, Xiangyu; Zheng, Rui; Chen, Yu (Frontiers in Immunology, 2025)
The immunocompromised population is susceptible to Legionella pneumonia. The diagnosis and treatment of Legionella pneumonia in immunocompromised individuals are challenging clinical endeavors. Previous studies have identified Legionella pneumonia as a potential cause of organizing pneumonia (OP), however, the association between Legionella pneumonia and OP has not received enough clinical attention. We retrospectively evaluated a case involving Legionella micdadei infection and OP in a patient with myelodysplastic syndrome and concurrent Sweet syndrome. The diagnosis of Legionella micdadei pneumonia was confirmed through various methods: metagenomic next generation sequencing (mNGS), Giemsa-staining and fluorescence in situ hybridization of lung tissue, as well as serum immunofluorescence antibody testing. Histopathological analysis of lung tissue revealed OP. The patient was successfully treated with a combination of antibiotics and low-dose glucocorticoids. In immunocompromised individuals, mNGS was capable of detection non-Legionella pneumophila serogroup 1. The pathological examination is important for identifying secondary OP and provides the evidence for treatment with glucocorticoids.